Cancer Cytogenetics Methods and Protocols - Campbell, Lynda J.; Campbell, Lynda J. (Methods in Molecular Biology,, 2011)
Cytogenetic studies of malignancy have become an essential tool in the clinical management of cancer patients. Cancer Cytogenetics: Methods and Protocols presents eminently practical key cytogenetic and FISH techniques for every stage of diagnostic service. Experts in the field describe detailed cytogenetic analysis methods, fluorescence in situ hybridization and array methods currently being applied to investigate and diagnose different varieties of cancer. Written in the highly successful Methods in Molecular Biology™ series format, chapters contain introductions to their respective topics, lists of the necessary materials and reagents, and step-by-step, readily reproducible laboratory protocols. The authors of the various chapters have also provided extensive notes to guide individuals who are new to these methods through the pitfalls that bedevil all such testing.             Authoritative and accessible, Cancer Cytogenetics: Methods and Protocols serves as an ideal guide to scientists of all backgrounds, allowing them to either establish new techniques in their laboratories or find the different variations of standard methods helpful in improving their results.